2019
DOI: 10.1002/tox.22752
|View full text |Cite
|
Sign up to set email alerts
|

T‐2 toxin downregulates LHCGR expression, steroidogenesis, and cAMP level in human cumulus granulosa cells

Abstract: Our goals were to investigate whether environmentally relevant doses of T‐2 toxin can affect human ovarian granulosa cells' function and to reveal the potential mechanism of T‐2 toxin's action. Results showed that T‐2 toxin strongly attenuated luteinizing hormone/choriogonadotropin receptor (LHCGR) mRNA expression in follicle‐stimulating hormone (FSH)‐stimulated human cumulus granulosa cells. Addition of human chorionic gonadotropin was not able to elicit maximal response of ovulatory genes amphiregulin, epire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…T-2 is the most toxic type A trichothecene mycotoxin, and the ubiquitous presence of T-2 in the natural environment has been reported to be a risk factor for cereals, animals, and humans . T-2 has toxin effects on neuronal cells, intestinal cells, and ovarian granulosa cells . Reports have proved that T-2 was primarily localized within the phagocytic elements of the duodenal lamina propria, especially neutrophils, and it also potentiated neutrophil counts in the lungs of mice when mice were given T-2. , Heterophils are phagocytic cells that have a wide range of antimicrobial activity, and heterophils release HETs to form the first line of the innate immune response against invading microbial pathogens in chickens. , In addition to the well-known protective role in the innate immune system, ET overproduction also has potentially harmful effects .…”
Section: Discussionmentioning
confidence: 99%
“…T-2 is the most toxic type A trichothecene mycotoxin, and the ubiquitous presence of T-2 in the natural environment has been reported to be a risk factor for cereals, animals, and humans . T-2 has toxin effects on neuronal cells, intestinal cells, and ovarian granulosa cells . Reports have proved that T-2 was primarily localized within the phagocytic elements of the duodenal lamina propria, especially neutrophils, and it also potentiated neutrophil counts in the lungs of mice when mice were given T-2. , Heterophils are phagocytic cells that have a wide range of antimicrobial activity, and heterophils release HETs to form the first line of the innate immune response against invading microbial pathogens in chickens. , In addition to the well-known protective role in the innate immune system, ET overproduction also has potentially harmful effects .…”
Section: Discussionmentioning
confidence: 99%
“…The antisteroidogenic effect of T-2 toxin was also observed in human cumulus GCs. Furthermore, T-2 toxin exposure decreased the expression of the ovulatory genes amphiregulin, epiregulin, and P receptor in human cumulus GCs, confirming that T-2 toxin has an antiovulatory effect . T-2 toxin exposure induced oxidative stress in porcine GCs by increasing the ROS content and reducing the activities of SOD and GSH-Px .…”
Section: Effect Of T-2 Toxin On the Female Reproductive Systemmentioning
confidence: 65%
“…Furthermore, T-2 toxin exposure decreased the expression of the ovulatory genes amphiregulin, epiregulin, and P receptor in human cumulus GCs, confirming that T-2 toxin has an antiovulatory effect. 51 T-2 toxin exposure induced oxidative stress in porcine GCs by increasing the ROS content and reducing the activities of SOD and GSH-Px. 52 Wu et al reported that treatment with T-2 toxin leads to rat ovarian GC apoptosis caused by oxidative stress.…”
Section: Effect Of T-2mentioning
confidence: 97%
“…The study was approved by the Ethics Committee of the Clinical Center of Vojvodina (approval number: 00-313), and signed informed consent was obtained from each participant. The exclusion criteria and the protocol for obtaining and isolating granulosa cells are described in [ 23 ].…”
Section: Methodsmentioning
confidence: 99%